Effectiveness of M-Paspor Applications in Aspects of Public Service and E-government - Pratama, Reza Akbar; Utami, Dana Alya (Jurnal Ilmiah Kajian Keimigrasian, 2023)
Utilization of technology in public services promises effectiveness and efficiency to help all human work lines because it can accelerate the work process done. The embodiment of e-government can be manifested as a form of utilizing technology in the public service sector. The M-Passport app is one of the implementations of e-government in the immigration field. The implementation of M-passport apps will be reviewed effectively whether they can realize effectiveness in public-e-government services. This can be seen from the implementation of passport applications which are getting easier and faster with the help of technology and systems that exist in the M-Paspor Application. This also supports the implementation of e-government-based public services and helps oversee social distancing policies during the Covid-19 pandemic in Indonesia so that we can continue to provide optimal immigration